A sociologia econômica e o capitalismo em Schumpeter à luz de Swedberg e Shionoya - Heringer, Bruno Pacheco (2024)
This dissertation sets out to investigate a field of research present in Joseph Schumpeter’s work, namely, economic sociology as a field of study of the economist. Constituting an institutional and evolutionary analysis of economic phenomena, it is argued that the comprehension of capitalism as an historical process is one of its main applications. Although his contribution to the field is concentrated in the second part of Capitalism, Socialism and Democracy, there are traces of economic sociology scattered in other writings of his, and its origins lie mainly in the German Historical School of Economics. In order to better understand this contribution our initial bibliographical review also rest upon two authors who organized the methodological foundations and substantive applications of schumpeterian economic sociology: Richard Swedberg and Yuichi Shionoya. Based on a systematic review of literature by searching terms related to a research question regarding the schumpeterian understanding of capitalism from the perspective of economic sociology, we’ve selected articles whose contributions could be identified with aspects of Schumpeter’s economic sociology, organized along six thematic axes. In what follows, we’ve compared such contributions with the interpretations of Swedberg and Shionoya, a discussion which provided both a better understanding of Schumpeter’s economic sociology and allowed a suggestion of a schumpeterian research program in the field. The results attained through our investigation underscored the importance of considering economic sociology not only to better understand Schumpeter’s work, but also as an indispensable analytical tool to a correct understanding of the nature and logic of capitalism